Democratic State and Democratic Society Institutional Change in the Nordic Model - Engelstad, Fredrik; Holst, Cathrine; Aakvaag, Gunnar C. (De Gruyter, 2019)
This book focuses on institutional change in Nordic societies. Among the Nordics, the main emphasis is on Norway, in many ways the best example of neo-corporatism. The main emphasise is put on the interplay of democracy and social institutions.